Aberrantly elevated suprabasin in the bone marrow as a candidate biomarker of advanced disease state in myelodysplastic syndromes. Issue 10 (11th August 2020) - Pribyl, Miroslav; Hubackova, Sona; Moudra, Alena; Vancurova, Marketa; Polackova, Helena; Stopka, Tomas; Jonasova, Anna; Bokorova, Radka; Fuchs, Ota; Stritesky, Jan; Salovska, Barbora; Bartek, Jiri; et al.
Abstract : Myelodysplastic syndromes (MDS) are preleukemic disorders characterized by clonal growth of mutant hematopoietic stem and progenitor cells. MDS are associated with proinflammatory signaling, dysregulated immune response, and cell death in the bone marrow (BM). Aging, autoinflammation and autoimmunity are crucial features of disease progression, concordant with promoting growth of malignant clones and accumulation of mutations. Suprabasin ( SBSN ), a recently proposed proto‐oncogene of unknown function, physiologically expressed in stratified epithelia, is associated with poor prognosis of several human malignancies. Here, we showed that SBSN is expressed in the BM by myeloid cell subpopulations, including myeloid‐derived suppressor cells, and is secreted into BM plasma and peripheral blood of MDS patients. The highest expression of SBSN was present in a patient group with poor prognosis. SBSN levels in the BM correlated positively with blast percentage and negatively with CCL2 chemokine levels and lymphocyte count. In vitro treatment of leukemic cells with interferon‐gamma and demethylating agent 5‐azacytidine (5‐AC) induced SBSN expression. This indicated that aberrant cytokine levels in the BM and epigenetic landscape modifications in MDS patients may underlie ectopic expression of SBSN . Our findings suggest SBSN as a candidate biomarker of high‐risk MDS with a possible role in disease progression and therapy resistance. Abstract : Aberrantly expressed suprabasin ( SBSN ) is a novel biomarker in myelodysplastic syndrome (MDS) patients. The highest levels of SBSN, secreted from myeloid subpopulations, including myeloid‐derived suppressor cells, are detectable within bone marrow (BM) and peripheral blood plasma of poor prognosis MDS subgroup. SBSN negatively correlated with BM T cells and CCL2 levels indicating immunosuppressive milieu in BM of MDS patients.